The depiction of preferred and needed autonomous learning method among Generation Z in Universitas Aisyisyah Yogyakarta - Setya Putri Rahayu (Universitas Merdeka Malang, 2019)
The study aims in investigating the rate of students who have applied autonomous learning behavior, in analyzing how students learn English, how they maximize the use of new technology in learning process, and what students prefer and need in mobile application that can boost their spirit in developing autonomous learning through new technology. Mixed method with total sampling as many as 206 students is applied to analyze the width and depth of topic studied. Questionnaire and structured interview were employed to obtain the studied data. The study found that low rate of developing autonomous learning (less than 30%) was still shown by students, and students had not maximized the use of new technology to boost to learn English as a foreign language. Moreover, the study also reveals that students prefer and need mobile application which owns dictionary-like feature with complete explanation on each word, what the word means and how the word is used. In addition, good visualization also becomes a plus value in a mobile application. DOI:10.26905/enjourme.v4i2.3595